Regional Economic Outlook, October 2015 : Sub-Saharan Africa. (Regional Economic Outlook, 2015)
Growth in sub-Saharan Africa has weakened after more than a decade of solid growth, although this overall outlook masks considerable variation across the region. Some countries have been negatively affected by falling prices of their main commodity exports. Oil-exporting countries, including Nigeria and Angola, have been hit hard by falling revenues and the resulting fiscal adjustments, while middle-income countries such as Ghana, South Africa, and Zambia are also facing unfavorable conditions. This October 2015 report discusses the fiscal and monetary policy adjustments necessary for these countries to adapt to the new environment. Chapter 2 looks at competitiveness in the region, analyzing the substantial trade integration that accompanied the recent period of high growth, and policy actions to nurture new sources of growth. Chapter 3 looks at the implications for the region of persistently high income and gender inequality and ways to reduce them.